2008
DOI: 10.1162/qjec.2008.123.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Betting on Hitler—The Value of Political Connections in Nazi Germany*

Abstract: This paper examines the value of connections between German industry and the Nazi movement in early 1933. Drawing on previously unused contemporary sources about management and supervisory board composition and stock returns, we find that one out of seven firms, and a large proportion of the biggest companies, had substantive links with the National Socialist German Workers' Party. Firms supporting the Nazi movement experienced unusually high returns, outperforming unconnected ones by 5% to 8% between January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
227
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 374 publications
(248 citation statements)
references
References 29 publications
9
227
0
1
Order By: Relevance
“…To get a more precise measure of all dismissals I complement the information in the "List of Displaced German Scholars" with information from other sources. 9 The main additional source is the "Biographisches Handbuch der deutschsprachigen Emigration nach 1933 -Vol. II : The arts, sciences, and literature".…”
Section: Data On Dismissed Scholarsmentioning
confidence: 99%
See 1 more Smart Citation
“…To get a more precise measure of all dismissals I complement the information in the "List of Displaced German Scholars" with information from other sources. 9 The main additional source is the "Biographisches Handbuch der deutschsprachigen Emigration nach 1933 -Vol. II : The arts, sciences, and literature".…”
Section: Data On Dismissed Scholarsmentioning
confidence: 99%
“…Recently other economists have analyzed aspects of the Nazi rise to power. Ferguson and Voth (2008), for example, show that …rms supporting the Nazi movement experienced unusually high stock-market returns in the …rst months of the Nazi regime. The …ndings of my paper may also lead to a better understanding of similar events which occurred in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a number of studies have computed the economic advantages for firms' shareholders of being connected at the board level with politicians. For example, Ferguson and Voth (2008) show that firms connected to the Nazi party experienced positive abnormal returns associated to the rise of Hitler's party to the German government. 15 Elsewhere (see Bel and Trillas 2005) it has been suggested that corporate governance in large Spanish firms give a lot of discretion to managers, and that they may take advantage of this great discretion by sharing rents with politicians in exchange for favours to political parties, in the form of appointing party cronies, funding media empires or supporting particular policies.…”
Section: Testing the Impact Of Political Connectionsmentioning
confidence: 99%
“…Fisman, 2001, Diermer et al, 2005, Ferguson and Voth, 2008, and Acemoglu et al 2010. We assume that access to such rents increases with membership in elite groups; for example, belonging to the same restricted club may facilitate connections between appointed politicians and entrepreneurs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%